A 10-Week Block of Combined High-Intensity Endurance and Strength Training Produced Similar Changes in Dynamic Strength, Body Composition, and Serum Hormones in Women and Men - Taipale, Ritva S.; Forssell, Jaakko; Ihalainen, Johanna K.; Kyröläinen, Heikki; Häkkinen, Keijo (Frontiers in Sports and Active Living, 2020)
Purpose: To examine the potential sex differences in adaptations to combined endurance and strength training in recreationally endurance trained (eumenorrheic) women (n = 9) and men (n = 10). Methods: Isometric (ISOMmax) and dynamic bilateral leg press (1RM), countermovement jump (CMJ), running performance (3,000 m time trial), lean mass and body fat % (LEAN and FAT% determined by dual X-ray absorptiometry) as well as serum testosterone and cortisol (TES and COR, respectively, measured using hormone-specific immunoassay kits) were examined before a control period and pre, mid, and post a supervised 10-week combined high-intensity interval endurance training (4 × 4 min intervals and 3 × 3 × 100 m repeated sprints) and mixed maximal and explosive strength training. No more than 2 weeks separated training and testing for either women or men and all women were tested in the early follicular phase of the menstrual cycle to minimize the possible influence of menstrual cycle phase on performance measures. Results: Absolute and relative changes in 1RM, CMJ, 3,000 m, LEAN, and FAT% were similar between groups. The only statistically significant differences observed between groups were observed at post and included a larger Δ% increase in ISOMmax force in men and a relatively greater Δ% decrease in serum TES in women. Conclusion: Women and men can achieve similar relative adaptations in dynamic maximal strength and CMJ as well as endurance performance gains and body composition over the same high-intensity 10-week combined program, although relative adaptations in TES may differ.